Gas-phase triggered phase evolution in pressure-less sintered LiF doped Mg-Al spinel. Issue 10 (August 2021) - Müller, Mathis M.; Stricker, Kerstin; Kleebe, Hans-Joachim
Highlights: LiF is one of the most promising sintering aid to fully densify spinel ceramics. However, the phase evolution is not completely understood. A number of interactions were postulated, including a wetting de-wetting mechanism and the formation of transient phases like LiAlO2 or MgF2. The formation of LiAlO2 was shown for the first time by means of electron microscopy in combination with x-ray diffraction methods. Moreover, the formation of a second generation of Mg-Al spinel was shown to be the result of a recombination of solid LiAlO2 and a gas phase. Shown results will influence further efforts in this system since a gaseous phase hinders full densification and thus full transparency. Abstract: Within the studies of the LiF-MgAl2 O4 system, a dissolution - reprecipitation process is postulated at high pressure synthesis, involving LiAlO2 and MgF2 as transient phases. Heating experiments at atmospheric pressure, combined with a dedicated sample geometry enabled the identification of LiAlO2 and MgO via XRD and, for the first time, with electron microscopic examinations. Moreover, it is shown that a second generation of spinel precipitates as the result of a gas-phase reaction. The involvement of a gaseous phase is seen as the major reason, why it seems impossible to produce transparent spinel in a pressure-less sintering regime.